Computational Methods for the Integrative Analysis of Genomics and Pharmacological Data - Caroli, Jimmy; Dori, Martina; Bicciato, Silvio (Frontiers in Oncology, 2020)
Since the pioneering NCI-60 panel of the late ‘80s, several major screenings of genetic profiling and drug testing in cancer cell lines have been conducted to investigate how genetic backgrounds and transcriptional patterns shape cancer response to therapy and to identify disease-specific genes associated with drug response. Historically, pharmacogenomics screenings have been largely heterogeneous in terms of investigated cell lines, assay technologies, number of compounds, type and quality of genomic data, and methods for their computational analysis. The analysis of this enormous and heterogeneous amount of data required the development of computational methods for the integration of genomic profiles with drug responses across multiple screenings. Here, we will review the computational tools that have been developed to integrate cancer cell lines genomic profiles and sensitivity to small molecule perturbations obtained from different screenings.